2012
DOI: 10.5194/amt-5-657-2012
|View full text |Cite
|
Sign up to set email alerts
|

Mobility particle size spectrometers: harmonization of technical standards and data structure to facilitate high quality long-term observations of atmospheric particle number size distributions

Abstract: Abstract. Mobility particle size spectrometers often referred to as DMPS (Differential Mobility Particle Sizers) or SMPS (Scanning Mobility Particle Sizers) have found a wide range of applications in atmospheric aerosol research. However, comparability of measurements conducted world-wide is hampered by lack of generally accepted technical standards and guidelines with respect to the instrumental setup, measurement mode, data evaluation as well as quality control. Technical standards were developed for a minim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
491
2
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 706 publications
(510 citation statements)
references
References 58 publications
16
491
2
1
Order By: Relevance
“…see Standard Deviation in figure box). The intercomparison confirmed that MHD SMPS system errors were well within general uncertainties derived for this type of instrument (±10 % for size in the range of 20 -200 nm and ±4 % for number) 45 .…”
Section: Aerosol Sizing and Counting Instrument Uncertaintiessupporting
confidence: 75%
“…see Standard Deviation in figure box). The intercomparison confirmed that MHD SMPS system errors were well within general uncertainties derived for this type of instrument (±10 % for size in the range of 20 -200 nm and ±4 % for number) 45 .…”
Section: Aerosol Sizing and Counting Instrument Uncertaintiessupporting
confidence: 75%
“…Table 1 summarizes the instrumentation on board the ATR-42 airplane used in this study. The scanning mobility particle sizer (SMPS) with an accuracy of 5 % (Wiedensohler et al, 2012) and the ultra high-sensitivity aerosol spectrometer (UHSAS) with an accuracy of 10 % (Cai et al, 2008) are used for measuring aerosol number size distribution in the submicron range. The wing-mounted Forward Scattering Spectrometer Probe (FSSP-300) with an accuracy of 30 % (Baumgardner et al, 1992) and the in-cabin GRIMM OPC (sky OPC 1.129) with an accuracy of 10 % were used to measure the optical size distributions in the diameter nominal size range between 0.28 and 20 µm and between 0.3 and 32 µm, respectively.…”
Section: Airborne Measurementsmentioning
confidence: 99%
“…On top of the container a PM 10 inlet followed by a self-regenerating diffusion drier was placed (Tuch et al, 2009), maintaining the relative humidity of the aerosol flow below 20 %. Inside the container -besides other instrumentation -a Mobility Particle Size Spectrometer (MPSS-type TROPOS; details of this instrument in Wiedensohler et al, 2012) was used to determine the particle number size distributions between 10 and 850 nm, and a Cloud Condensation Nucleus counter (CCNc, CCN-100, DMT Boulder, Roberts and Nenes, 2005) in combination with a differential mobility analyser (DMA) was used to measure CCN distributions between 25 and 300 nm.…”
Section: Measurement Sitesmentioning
confidence: 99%